Peningkatan Hasil Belajar Siswa Pada Pembelajaran Pendidikan Kewarganegaraan (PKn)Dengan Model Kooperatif Student Teams Achiement Divisions (STAD) di Sekolah Dasar - Edison, Tressiana Reski; Zuardi, Zuardi; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is motivated by the low of student learning outcomes in class IV SD Negeri 13 Koto Alam Kecamatan Padang Ganting.This study aim to describe the improvement of student learning outcomes on learning Civics by applying the model Cooperatif Tipe Student Teams Achievent Divisions (STAD) on the fourth grade students SD Negeri 13 Koto Alam Kecamatan Padang Ganting. Type of research is PTK by using qualitative and quantitative approach. The result of student learning cycle I 75,6 increased to 81,6 in cycle II. Thus, the learning of Civics by applying the Cooperatif Tipe Student Teams Achievent Divisions (STAD) on can improve the learning outcomes of Civics students grade IV SD Negeri13 Koto Alam Kecamatan Padang Ganting. Key Word :Result study, PKn, model STAD learning